Planning Challenges of the Coastal Tourism Development - Sánchez, Alberto (2005)
The article describes the current challenges related to the planning in the coastal areas emphasizing the chaos and anarchy existing nowadays in those areas where the 6.043 law on marine-coastal zone applies. The strategy of national regulation with requirements of quality and sustainability as well as the relationships at regional and local levels is structured. In the national planning, it focuses on the  importance  of  the  effects  of  binding guidelines among different levels in the fulfillment of the National Plan of Sustainable Tourism 2002-2012, making special emphasis on the arguments that justify the process of carrying out integral regulation  plans  in  each  of  the  development centers inside the tourism units.  Finally, it mentions the functionality of the coastal forest to guarantee tourist landscapes for the future and the current problematic in determining those borders by the Government.